Studi Kualitatif tentang Gaya Kepemimpinan Wanita dan Implikasinya terhadap Efektivitas Manajemen SDM pada Organisasi Mahasiswa fakultas Ekonomi dan Bisnis di Universitas Bangka Belitung - One Olivia Kusumawati; Sarmawati Sarmawati; Shadina Ningrum; Trie Yunike; Dian Prihardini Wibawa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to understand women's leadership styles and their implications for the effectiveness of human resource management in student organizations at the Faculty of Economics and Business, Bangka Belitung University. The research method used was a qualitative approach with descriptive methods, involving in-depth interviews, observation, and documentation. Informants were selected through purposive and snowball sampling until data saturation reached. The results indicate that female leaders employ a transformational leadership style that combines empathy, emotional intelligence, assertiveness, and two-way communication. This style increases employee engagement, participation, and solidarity, creates a supportive, fair, and productive work environment, while also encouraging individual capacity development within the organization. The study concludes that female leadership significantly improves the effectiveness of human resource management through a combination of emotional caring, motivation, and adaptive collaborative leadership practices. Keywords: Female Leadership, Transformational, Human Resource Management